2015
DOI: 10.3389/fmicb.2015.01372
|View full text |Cite
|
Sign up to set email alerts
|

The Scion/Rootstock Genotypes and Habitats Affect Arbuscular Mycorrhizal Fungal Community in Citrus

Abstract: Citrus roots have rare root hairs and thus heavily depend on arbuscular mycorrhizal fungi (AMF) for mineral nutrient uptake. However, the AMF community structure of citrus is largely unknown. By using 454-pyrosequencing of 18S rRNA gene fragment, we investigated the genetic diversity of AMF colonizing citrus roots, and evaluated the impact of habitats and rootstock and scion genotypes on the AMF community structure. Over 7,40,000 effective sequences were obtained from 77 citrus root samples. These sequences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
(80 reference statements)
1
20
0
1
Order By: Relevance
“…It is conceivable that soil fungi may be shaped not only by host cultivars or genotypes but also by the habitat environment. Indeed, previous studies reported that the structure of fungal communities can be driven by many environmental factors, such as pH, organic matter content [ 5 ], nutrient concentration, total N, phosphorus, salinity, and temperature [ 23 ]. We thus collected basic information on the soil during the peanut pod rot experiment for all six samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is conceivable that soil fungi may be shaped not only by host cultivars or genotypes but also by the habitat environment. Indeed, previous studies reported that the structure of fungal communities can be driven by many environmental factors, such as pH, organic matter content [ 5 ], nutrient concentration, total N, phosphorus, salinity, and temperature [ 23 ]. We thus collected basic information on the soil during the peanut pod rot experiment for all six samples.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their close relationships with plants, soil fungal communities are shaped by a number of biotic and abiotic factors [ 4 ]. Of particular note is that plant genotypes (different genotypes, i.e., different plant species or even different crop cultivars) also have been reported to have an impact on the genetic diversity of fungi based on some preliminary studies [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In both natural and agricultural ecosystems, bacteria and fungi in diverse taxonomic groups 44 are associated with plants, positively and/or negatively influencing the survival and growth of 45 their hosts (Vorholt 2012;Mendes et al 2013;Bai et al 2015;Peay et al 2016). An 46 increasing number of studies have shown that plant-associated microbes not only improve nutritional conditions of host plants but also increase plants' resistance to abiotic stresses (e.g., 48…”
Section: Abstract 20mentioning
confidence: 99%
“…Despite the apparent prevalence of the fungus in the soil, no severe outbreaks of Neocosmospora root rot were recorded in the years 2013 to 2016, particularly in areas where the pathogen was found to have previously caused major crop damage, such as Codenwarra Station in the Emerald region in 2007/2008 and 2011/2012. It iscommon for the abundance and spatial distribution of fungal communities to vary within the soil in response to the presence of a host or non-host plant as well as variations to the habitat environment such as pH or organic matter(Song et al 2015) along with soil nutrient concentration, available N and P, salinity levels and soil temperature(Tao et al 2015) Hao et al (2017). found that the abundance of fungi, both pathogenic and non-pathogenic fungi varied between peanut cultivars and sampling sites, likely as a result of this variation in habitat environment.…”
mentioning
confidence: 99%